2017
DOI: 10.1074/jbc.m117.794370
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic domain of T-cell receptor ζ associates with membranes in a dynamic equilibrium and deeply penetrates the bilayer

Abstract: Interactions between lipid bilayers and the membrane-proximal regions of membrane-associated proteins play important roles in regulating membrane protein structure and function. The T-cell antigen receptor is an assembly of eight single-pass membrane-spanning subunits on the surface of T lymphocytes that initiates cytosolic signaling cascades upon binding antigens presented by MHC-family proteins on antigen-presenting cells. Its ζ-subunit contains multiple cytosolic immunoreceptor tyrosine-based activation mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…This was also true for a CD3ε cytosolic tail peptide . In both cases, binding to the membrane induced folding of the otherwise unstructured peptides and required the presence of a basic rich sequence (BRS) in those peptides . Membrane binding of the ζ and CD3ε peptides shielded the ITAMs from phosphorylation in an in vitro kinase assay .…”
Section: Ligand‐regulated Changes In the Tcr Cytosolic Tailsmentioning
confidence: 81%
See 2 more Smart Citations
“…This was also true for a CD3ε cytosolic tail peptide . In both cases, binding to the membrane induced folding of the otherwise unstructured peptides and required the presence of a basic rich sequence (BRS) in those peptides . Membrane binding of the ζ and CD3ε peptides shielded the ITAMs from phosphorylation in an in vitro kinase assay .…”
Section: Ligand‐regulated Changes In the Tcr Cytosolic Tailsmentioning
confidence: 81%
“…It has been reported that these cytoplasmic tails bind to each other, and might thus form some defined structure by protein‐protein interactions . However, NMR and structural analyses only exist of isolated peptides corresponding to these tails, showing that these peptides are unstructured . It is therefore realistic to think that these peptides in isolation do not find their partners to fold into a common structure and therefore they were unstructured.…”
Section: Structural Information On the Complete Tcr Is Limitedmentioning
confidence: 99%
See 1 more Smart Citation
“…How these lipids relate to biological phospholipids is not known, but point to the possibility that other components of the phospholipid, other than the acidic head group, may be involved in regulating immune receptor binding dynamics and function. Remarkably, lipid association to any acidic, but not zwitterionic, phospholipids prevented CD3ζ CT phosphorylation by a recombinant Scr kinase in an in vitro assay and was due to deep embedding of the side chains within the bilayer . This led the authors to postulate for the first time a model in which the phosphorylation of CD3ζ chains of the TCR was prevented by sequestering the ITAM from kinases through electrostatic interaction‐driven dynamic membrane binding.…”
Section: Electrostatic Interaction‐driven Lipid Bindingmentioning
confidence: 99%
“…However, a previous in vitro study has showed that clustering of CD3ζ did not change its random-coil-like unstructured status (Sigalov et al, 2004). It is likely that LIC-CD3z remains dynamically membrane associated (Zimmermann et al, 2017) regardless of its clustering state. It should be also considered that previous work showed that ITAMs can still be phosphorylated by Lck in membrane-bound state (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 86%